A persistência do excesso de tensão no fundo como critério de estabilidade hidro-sedimentológica de canais de maré - Buckmann, Monica Frickmann Young (2019)
This work proposes a methodology for projecting the critical cross-sectional area of stable tidal inlets in hydro-sedimentological terms, with feasibility analysis. A stable tidal inlet can expel excess sediment deposited inside it, keeping its mouth clear, varying little over decades. The methodology is based on the persistence in which the shear stress exerted by the currents exceeds the critical mobility shear stress for the median diameter bottom sediment and conforms to well-established classical criteria for analysis of dynamic stability of tidal inlets. The research used computational modeling with analyses of 5985 cases involving idealized lagoon systems with one tidal inlet, with different tidal amplitudes, median sediment diameters, lagoon surface areas and channel geometries of the morphologically natural tidal inlets. It was found that the stable channels that satisfy the relations of O’Brien (P × Ac) show in its crosssectional area a persistence of excess shear stress in a range between 65% and 85% of the time of a tidal cycle of average spring tidal cycle. The analysis concludes that, during a lunar month, for a channel to be viable, its projected critical cross-sectional area of a stable tidal inlet must have currents that maintain persistence of excess shear stress at the bottom of the critical area in 75% of the time, with a tolerance of ± 10%. This methodology is more realistic because it includes the local sediment, morphological relationships of natural cross-sectional areas, tidal variability in the monthly cycle, allowing to define the viability of projected tidal inlets by indicating a more guaranteed critical cross-sectional area geometry. It is worth remembering that the classical criteria indicate a supposedly stable critical cross-sectional area, but without guarantee of viability.